Giant reed (Arundo donax L.) for biogas production: land use saving and nitrogen utilisation efficiency compared with arable crops - Dragoni, Federico; Ragaglini, Giorgio; Corneli, Elisa; Nassi o Di Nasso, Nicoletta; Tozzini, Cristiano; Cattani, Sergio; Bonari, Enrico (Italian Journal of Agronomy, 2015)
Aiming to improve the sustainability of biogas supply chains, the research for alternative feedstocks is a key issue and giant reed (Arundo donax L.) is a promising no-food crop to be used in anaerobic digestion. In fact, giant reed is a perennial species characterised by low nutrient requirements and is able to provide promising biogas yields. Its suitability for anaerobic digestion is influenced by harvest time, since plant characteristics vary noticeably along the season. Moreover, ensiling is a storage technique that can assure a good preservation of the biomass over time, but also influence the methane yields. Therefore, the aim of this study was to assess the suitability for biogas production of giant reed silage, according to different cutting regimes, and to evaluate the efficiency in saving land and nitrogen for fuelling biogas plants, in comparison with maize and two sorghum varieties. Methane yields per hectare (Nm3 CH4 ha–1) were determined by multiplying the biochemical methane potential of each substrate by the aboveground biomass of the corresponding crop. The land use coefficient (LU), namely the land needed to fuel one kW power (ha kWe–1), was calculated from the estimated methane yields per hectare. Finally, nitrogen utilisation efficiency (NUtE), which is the ratio between the estimated methane yield and the nitrogen uptake per hectare (Nm3 CH4 kgN–1), was determined for each crop species and according to the harvest time and frequency of giant reed. Overall, a good suitability for ensiling was observed in giant reed. When harvested in September, the crop yielded about 9900 Nm3 CH4 ha–1, while in double harvest systems biomethane was about 12,000 Nm3 CH4 ha–1, +35% and +70% than maize and sorghum respectively. Moreover, giant reed under double harvest management was the most land-conservative option, as LU was about 0.22 ha kWe–1, while in annual crops it was about 0.35 ha kWe–1. The higher NUtE was observed in single harvests (up to 64 Nm3 CH4 kgN–1), while double harvests showed remarkably lower values, averaging 48 Nm3 CH4 kgN–1. Annual crops were less efficient, since NUtE ranged from 28 Nm3 CH4 kgN–1 (maize) to 40 Nm3 CH4 kgN–1 (fibre sorghum). In conclusion, giant reed can be an alternative for biogas making, potentially providing land and nitrogen savings compared with conventional annual crops.